Investigation on the Effect of Ammonia Distribution on Selective Catalytic Reduction Conversion Efficiency - Tian, Xinna; Zhang, Wenping; Xiao, Youhong; Zhou, Peilin (Asian Journal of Chemistry, 2012)
The effect of ammonia distribution upstream selective catalytic reduction converter on selective catalytic reduction conversion efficiency has been studied in this paper. The results indicate that the more uniform ammonia concentration distribution upstream converter is, the higher NOx reduction rate and lower NH3 slip can be achieved. By using static mixers fixed in the pipeline upstream converter, ammonia and exhaust streams can be mixed effectively on the limitation of mixing distance for marine selective catalytic reduction system. Different kinds of static mixers could lead to different degree of mixing between ammonia and exhaust streams, which will affect selective catalytic reduction conversion efficiency directly. Then comparing with the complete mixing degrees of ammonia and exhaust streams, selective catalytic reduction conversion efficiency can be used as an evaluation index for static mixers. Based on CFD method, the effect of mixing degrees of different static mixers on selective catalytic reduction conversion efficiency can be obtained by simulating current commercial catalysts with several different kinds of static mixers such as GK mixer, SK mixer, contour mixer, star-shaped mixer. The trend of NOx reduction rate and NH3 slip changing with ammonia distribution and velocity distribution before selective catalytic reduction catalyst layers can be summarized by analyzing the simulating data. The results can be used to help engineering applications.